Metabolic disposition and excretion of quinocetone in rats, pigs, broilers, and carp - Li, Juan; Huang, Lingli; Wang, Xu; Pan, Yuanhu; Liu, Zhaoying; Chen, Dongmei; Tao, Yanfei; Wu, Qinghua; Yuan, Zonghui (Food and chemical toxicology, 2014)
Excretion, disposition, and metabolism of [(3)H]-quinocetone in rats, pigs, broilers, and carp following oral administration were investigated. After a single p.o. dose, total radioactivity was rapidly excreted, with ⩾94% in all species within 14 days. Fecal excretion of radioactivity was 68% and 65% of the administered dose in rats and pigs, respectively, with the remainder excreted in the urine. Six hours after the last of seven daily oral administrations of (3)H-labeled QCT, radioactivity was found to be distributed throughout all tissues, with the majority of radioactivity cleared within 7 days, and elimination was the slowest from the liver and kidney. QCT was extensively metabolized in all of the species, and the primary changes included N-O group reduction, carbonyl group reduction, double bond reduction, and hydroxylation. The major tissue metabolites of QCT were Q2, Q4, Q5, Q8, and Q9 in rats; Q1, Q2, Q3, Q4, and Q5 in pigs; Q1, Q2, Q3, Q4, and Q7 in broilers; and Q1, Q2 in carp. This confirmed the potential link between QCT metabolism through N-O group reduction and its organ toxicity. The results of the present study provide important data that could help understand the relationship between the toxicities and metabolic disposition of QCT.
Keywords: tritium; kur domácí; Male; Excretion; Radioactivity isotope tracing; Chickens; potkani Wistar; Tritium; Animals; Feces; Tissue Distribution; Quinoxalines; zvířata; Quinocetone; Metabolism; Toxicology; mužské pohlaví; Administration, Oral; tkáňová distribuce; chinoxaliny; kapři; Sus scrofa; Rats, Wistar; ženské pohlaví; feces; Female; aplikace orální; Carps; Disposition